Densitas Schooling Ikan Pelagis pada Musim Timur Menggunakan Metode Hidroakustik di Perairan Selat Bangka - Fauziyah Fauziyah; Ningsih E.N Ningsih E.N; Wijopriono Wijopriono (Faculty of Mathtmatics and Natural Sciences, 2010)
Acoustic survey has been done in July 19th - 24th 2008 at Bangka Strait. The aim of this study was to analysis pelagic fish school migration during northeast monsoon using split beam scientific echosounder. During northeast monsoon, pelagic fish at Bangka Strait was dominated small pelagis fish based on Pasaribu, 1998. This study reports analyses of data from 53 pelagic fish schools and dominated with Target Strength (-50) - (-47) dB. All schools were recorded at depths 5-15 m. The fish also formed the school during daytime. Density of pelagic fish school was 0-300 ind/1000m3 with dominated between 101-300 ind/1000m3. In general, the swimming directions of pelagic fish school migrate to south until south east to continent (Java Sea).